JARINGAN PERDAGANGAN BERAS DAN DINAMIKA PELABUHAN EKSPOR DI SULAWESI SELATAN PADA 1930-AN - Syafaat Rahman Musyaqqat (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2021)
As the National rice barn, the Southern Sulawesi is often associated with the green revolution of the New Order Regime, especially since Indonesia succeeded the rice self-sufficency in 1984. Furthermore, Southern Sulawesi has an important role as rice supplier in Indonesia which was proven in 1930s. The state control is one of main factors supporting Southern Sulawesi’s success, along with another factor particularly environmental conditions and irrigation development. This article discusses the rice trade network and its relationship to the dynamics of export ports in Southern Sulawesi in the 1930s. By applying the historical method, this study employed primary sources, such as archives, journals, newspapers, and magazines. The findings show that the rice trade during the 1930s experienced a significant development as the state involved in the trade in 1933. The increase was seen in the trading system and the amount of exported rice. The increase which was seen in the trading system and the amount of exported rice indicates the significance of Southern Sulawesi as one of the rice barns in the Dutch East Indies. By describing the production areas, involved actors, export ports, and trade networks, this study shows the relationship between intra- and inter-regional trade.